Localization of interleukin-1 alpha, type 1 interleukin-1 receptor and interleukin-1 receptor antagonist in the synovial membrane and cartilage/pannus junction in rheumatoid arthritis. - Deleuran, B; Chu, C; Field, M; Brennan, F; Katsikis, P; Feldmann, M; Maini, R (1992)
Using monoclonal antibodies and immunohistochemical techniques we have investigated the presence and distribution of interleukin-1 alpha (IL-1 alpha), type 1 IL-1 receptor (IL-1R1) and of interleukin-1 receptor antagonist (IL-1ra) in synovial tissue from 18 rheumatoid arthritis (RA) and eight osteoarthritis (OA) patients and in eight normal synovial tissue samples. IL-1 alpha and IL-1R1 were found in all of the samples examined. In RA, there were a large number of synovial cells expressing IL-1 alpha and IL-1R1, with 85 and 90% positive cells in the lining layer, 45 and 80% in the interaggregate area, and 90% of the vascular endothelial cells. In the lymphoid aggregates, 20% of the cells contained IL-1 alpha and 70% expressed IL-1R1. IL-1 alpha and IL-1R1 expressing cells showed a similar distribution in OA synovial membrane, but there was a smaller number of positive cells in the deeper area; and the staining intensity was lower. In contrast to IL-1 alpha and IL-1R1, IL-1ra was found only in 10/18 RA, 5/8 OA and 2/8 normal tissue samples. IL-1ra was detected in 35% of RA and 45% OA lining layer cells; 25% RA and 35% OA vascular endothelium; 10% RA and 15% OA interstitial cells and 30% cells in RA lymphoid aggregate. The staining intensity in both RA and OA tissues was comparably low. The presence of IL-1ra in RA and OA tissues was confirmed by Northern blot analysis for IL-1ra mRNA.(ABSTRACT TRUNCATED AT 250 WORDS)